2016
DOI: 10.1152/ajpgi.00299.2015
|View full text |Cite
|
Sign up to set email alerts
|

An organotypic slice model for ex vivo study of neural, immune, and microbial interactions of mouse intestine

Abstract: Organotypic tissue slices provide seminatural, three-dimensional microenvironments for use in ex vivo study of specific organs and have advanced investigative capabilities compared with isolated cell cultures. Several characteristics of the gastrointestinal tract have made in vitro models for studying the intestine challenging, such as maintaining the intricate structure of microvilli, the intrinsic enteric nervous system, Peyer's patches, the microbiome, and the active contraction of gut muscles. In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…The mechanisms of signaling between neural fibers and crypt epithelia remains unclear. Incorporation of the thymidine analog EdU into DNA has previously been used to quantify the rate of epithelial cell production in mouse small intestine both in vivo (Krndija et al, ()) and ex vivo ( Schwerdtfeger et al, ). In this study, the number of glycan synthesizing goblet cells that were also undergoing DNA synthesis as marked by EdU was substantially decreased in slices treated with the VIP receptor antagonist VPACa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of signaling between neural fibers and crypt epithelia remains unclear. Incorporation of the thymidine analog EdU into DNA has previously been used to quantify the rate of epithelial cell production in mouse small intestine both in vivo (Krndija et al, ()) and ex vivo ( Schwerdtfeger et al, ). In this study, the number of glycan synthesizing goblet cells that were also undergoing DNA synthesis as marked by EdU was substantially decreased in slices treated with the VIP receptor antagonist VPACa.…”
Section: Discussionmentioning
confidence: 99%
“…This study uses organotypic intestinal slices (Schwerdtfeger, Nealon, Ryan, & Tobet, 2019;Schwerdtfeger, Ryan, & Tobet, 2016) as a platform for investigating neural -goblet cell interactions in mouse ileum ex vivo. This intestinal slice method allowed for use of three pharmacological tools for altering goblet cell function ex vivo in a cellularly heterogenous tissue.…”
mentioning
confidence: 99%
“…PCTS are believed to have advantages over organoids and organ-on-a-chip (discussed later), as they represent all regions of the tissue [91]. It has been reported that murine intestine is maintained for 6 days in the presence of normal neuronal, muscular, and mucosal structures with contractibility functions and some immune responses, therefore, representing a more holistic intestinal organ [93]. Additionally, in the absence of antibiotic media, some aerobic commensal microbes can be maintained [93].…”
Section: Tissue Slicesmentioning
confidence: 99%
“…It has been reported that murine intestine is maintained for 6 days in the presence of normal neuronal, muscular, and mucosal structures with contractibility functions and some immune responses, therefore, representing a more holistic intestinal organ [93]. Additionally, in the absence of antibiotic media, some aerobic commensal microbes can be maintained [93]. Although this system holds great promise to study holistically the complex mechanisms that underpin healthy gut functions and disease in a 3D physiologically relevant environment, further work is required to maintain anaerobic microbes that are predominately found within the intestinal environment [94].…”
Section: Tissue Slicesmentioning
confidence: 99%
“…A number of intestinal explant models were focused on characterising and maintaining healthy tissue in vitro. A modified organotypic slice model, using a similar protocol to that previously used in brain,71 was capable of maintaining 250-μm thick mouse intestinal slices in serum-free media, without antibiotics, for up to 6 days ex vivo 97. Unfortunately, details of tissue health were minimal in the early colon studies, which also used serum (5%-15% foetal calf serum).…”
mentioning
confidence: 99%